Involvement of an AFP1-binding site in cell-specific transcription of the pre-S1 region of the human hepatitis B virus surface antigen gene. - Nakao, K (1989)
Human hepatitis B virus infection is characterized by a high degree of hepatotropism which may be due to the dependency of viral genes on specific host factors for their expression. To learn more about such a requirement and the molecular basis of the viral tissue tropism we analyzed the promoter function in the pre-S1 region of the surface antigen gene. DNase I footprinting and competition gel retardation assays showed that a sequence with an AT-rich core (AT motif) in the pre-S1 promoter region interacts with AFP1, a hepatoma nuclear factor that binds to the alpha-fetoprotein enhancer and promoter. Functional analysis of the pre-S1 AT motif by transient transfection assays showed that this element is important in cell-specific transcriptional initiation. These results suggest that AFP1 may be one of the factors determining the liver specificity of human hepatitis B virus.